The effect of initial fattening weight on sustainability of beef cattle production in feedlots - Demircan, V.
(Es, En)
Ilus., 33 ref.
Keywords: GANADO BOVINO; PRODUCCION; ENGORDE; ENERGIA; INTERCAMBIO DE ENERGIA; EFICACIA; ESPAÑA